Semantic program alignment for equivalence checking - Churchill, Berkeley; Padon, Oded; Sharma, Rahul; Aiken, Alex (PLDI, 2019)
We introduce a robust semantics-driven technique for program equivalence checking. Given two functions we find a trace alignment over a set of concrete executions of both programs and construct a product program particularly amenable to checking equivalence. We demonstrate that our algorithm is applicable to challenging equivalence problems beyond the scope of existing techniques. For example, we verify the correctness of the hand-optimized vector implementation of strlen that ships as part of the GNU C Library, as well as the correctness of vectorization optimizations for 56 benchmarks derived from the Test Suite for Vectorizing Compilers.